Elicitor induction of phenolic compound in suspension cultured rice cells inoculated with Xanthomonas oryzae pv. oryzae - P. VIDHYASEKARAN, K. RAJAPPAN* and (Indian Phytopathology, 2002)
Treatment of suspension cultured rice cells with an abiotic elicitor, nickel nitrate increased the total and ortho-dihydroxy phenolics content. Inoculation of rice cells with the bacterial blight pathogen Xanthomonas oryzae pv. oryzae (Xoo) decreasedthe phenolics content while, elicitor treatment of rice cells 24 h prior to inoculation with Xoo increased the phenolics content. A new phenolic compound (Rf = 0.63) was detected in-both elicitor treated and elicitor treated plus inoculated cells.